The role of benthic habitat mapping for science and managers: A multi-design approach in the Southeast Brazilian Shelf after a major man-induced disaster - Menandro, Pedro S.; Lavagnino, Ana Carolina; Vieira, Fernanda V.; Boni, Geandré C.; Franco, Tarcila; Bastos, Alex C. (Frontiers in Marine Science, 2022)
Seabed mapping is currently the baseline information for ocean management and conservation, and is an indispensable item within research and Marine Spatial Planning. Here, we use a case study and published data along the southeast Brazilian continental shelf to illustrate the concepts and ideas of potential benthic habitat mapping and the importance of having maps on different scales and the potential for using a multi-design approach. The case analysis presented here uses a regional map and distinct criteria (seabed geodiversity and biodiversity, and potential influence of a tailings plume) to define three areas along the continental shelf to be mapped in a high-resolution, as part of a marine monitoring program. The background of the case study is a tailing dam failure disaster that led to the input of iron ore tailings in the ocean, leading to a major environmental disaster. Three areas were chosen, including: a Marine Protected Area (MPA Costa das Algas), a major fishing ground (the Doce River prodelta/depocenter), and an understudied reef area (Forgotten Reefs). Potential benthic habitat mapping was carried out using acoustic surveys (multibeam echosounder acquiring bathymetry and backscatter) and ground-truthing (sediment samples and seafloor image). Results detailed the potential habitats throughout the three areas, providing primary information for the study of benthic habitats and their distribution. The multi-design approach indicated that although a regional analysis can indicate potential vulnerability as a first assessment approach, high-resolution potential habitat mapping (herein, 20 m or finer) is beneficial to evaluate and produce a higher-confidence level for decision-makers. Having an overall view of what and where to collect new and finer data would be best to identify vulnerable areas that, in this case study, could be threatened by plume dispersion and tailings accumulation. Our results support the delineation of priority areas aiming for monitoring, protection and guiding for other studies, besides the consolidation of habitat importance and the integration of various datasets through a hierarchical classification scheme. Although Brazil has never produced a regional or national habitat map for the entire continental margin, there are already conditions to plan, execute and maintain a habitat mapping program, partnering with Universities, Government Institutions (e.g., the Brazilian Navy), and the private sector. In the context of the UN Decade of Ocean Science targets, it is urgent to plan and implement a national database capable of supporting a habitat classification effort on a broader national scale, with the flexibility to support a multi-design or a multi-scale approach.